2010
DOI: 10.1002/prot.22826
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and inhibitor binding in cdc25 phosphatases

Abstract: Cdc25 phosphatases involved in cell cycle checkpoints are now active targets for the development of anti-cancer therapies. Rational drug design would certainly benefit from detailed structural information for Cdc25s. However, only apo- or sulfate-bound crystal structures of the Cdc25 catalytic domain have been described so far. Together with previously available crystalographic data, results from molecular dynamics simulations, bioinformatic analysis, and computer-generated conformational ensembles shown here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 77 publications
(163 reference statements)
1
30
3
3
Order By: Relevance
“…The global flexibility of Cdc25B has been debated in the literature . Previous simulations employing either molecular dynamics with the OPLS‐AA force field or a library of rotamers sampled by Monte Carlo suggested that the Cdc25B C‐terminal α ‐helix may (partially) unfold in solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The global flexibility of Cdc25B has been debated in the literature . Previous simulations employing either molecular dynamics with the OPLS‐AA force field or a library of rotamers sampled by Monte Carlo suggested that the Cdc25B C‐terminal α ‐helix may (partially) unfold in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The global flexibility of Cdc25B has been debated in the literature . Previous simulations employing either molecular dynamics with the OPLS‐AA force field or a library of rotamers sampled by Monte Carlo suggested that the Cdc25B C‐terminal α ‐helix may (partially) unfold in solution. NMR experiments presented previously for a truncated construct of the Cdc25B catalytic domain and obtained here for the complete catalytic domain show this C‐terminal α ‐helix is folded and has little flexibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34] Furthermore, backbone flexibility was applied to different therapeutically important targets. [36–38] For a recent review see Refs 39, 40…”
Section: Introductionmentioning
confidence: 99%